SARS-CoV-2–specific CD8+ T cell responses in convalescent COVID-19 individuals - Kared, Hassen; Redd, Andrew D.; Bloch, Evan M.; Bonny, Tania S.; Sumatoh, Hermi; Kairi, Faris; Carbajo, Daniel; Abel, Brian; Newell, Evan W.; Bettinotti, Maria P.; Benner, Sarah E.; Patel, Eshan U.; et al. (The Journal of clinical investigation, 2021)
Characterization of the T cell response in individuals who recover from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is critical to understanding its contribution to protective immunity. A multiplexed peptide-MHC tetramer approach was used to screen 408 SARS-CoV-2 candidate epitopes for CD8+ T cell recognition in a cross-sectional sample of 30 coronavirus disease 2019 convalescent individuals. T cells were evaluated using a 28-marker phenotypic panel, and findings were modelled against time from diagnosis and from humoral and inflammatory responses. There were 132 SARS-CoV-2-specific CD8+ T cell responses detected across 6 different HLAs, corresponding to 52 unique epitope reactivities. CD8+ T cell responses were detected in almost all convalescent individuals and were directed against several structural and nonstructural target epitopes from the entire SARS-CoV-2 proteome. A unique phenotype for SARS-CoV-2-specific T cells was observed that was distinct from other common virus-specific T cells detected in the same cross-sectional sample and characterized by early differentiation kinetics. Modelling demonstrated a coordinated and dynamic immune response characterized by a decrease in inflammation, increase in neutralizing antibody titer, and differentiation of a specific CD8+ T cell response. Overall, T cells exhibited distinct differentiation into stem cell and transitional memory states (subsets), which may be key to developing durable protection.